Kidney failure in the elderly due to hypothyroidism: a case report - Silva, Graziela Cristina Pichinin Ledo; Carneiro, Jaqueline Brotto; Tardelli, Cecília Carboni; Risso, Maviane; Ventura, Mauricio de Miranda (São Paulo Medical Journal, 2008)
CONTEXT: Hypothyroidism is more prevalent in the elderly and its symptoms can be confused with other changes due to aging. Doctors caring for the elderly need to be attentive to this diagnostic possibility. This case report case is notable not only because it presents a rare complication of hypothyroidism (kidney failure), but also because patients with chronic kidney failure of any etiology may suffer increased renal dysfunction as a result. CASE REPORT: This was a 66-year-old male outpatient with a history of generalized edema over the preceding eight years, with periods of worsening, that was intractable to treatment with diuretics. Physical examination revealed bradycardia (heart rate: 52 bpm), pallor, dry and infi ltrated skin, macroglossia, edema in the lower limbs and a palpable thyroid with hard consistency. Laboratory tests showed: creatinine 3.9 mg/dl; urea 95 mg/dl; potassium 6.0 mEq/l; thyroid-stimulating hormone > 100 mUI/ ml; triiodothyronine 0.01 ng/dl; free thyroxin 0.01 ng/dl; antithyroglobulin 31 IU/ml (normal values: < 40 IU/ml); antithyroperoxidase 85 IU/ml (normal values: < 15 IU/ml); creatinine clearance 30 ml/min/1.73 m2; and proteinuria 122 mg/24 h. After fi ve months of treatment with thyroxin (100 mcg/day), the patient returned without any symptoms and presented the following test results: urea 48 mg/dl; creatinine 1.4 mg/dl; creatinine clearance 67 ml/min/1.73 m2; potassium 4.2 mEq/l; thyroid-stimulating hormone: 20.85 mUI/ml; free thyroxin: 0.71 ng/dl. Hypothyroidism alone can cause renal impairment or worsen renal function in preexisting illnesses. Its treatment can stabilize the clinical condition, or possibly improve it.